Plant Microbiome Engineering: Expected Benefits for Improved Crop Growth and Resilience. Issue 12 (December 2020) - Arif, Inessa; Batool, Maria; Schenk, Peer M.
Abstract : Plant-associated microbiomes can boost plant growth or control pathogens. Altering the microbiome by inoculation with a consortium of plant growth-promoting rhizobacteria (PGPR) can enhance plant development and mitigate against pathogens as well as abiotic stresses. Manipulating the plant holobiont by microbiome engineering is an emerging biotechnological strategy to improve crop yields and resilience. Indirect approaches to microbiome engineering include the use of soil amendments or selective substrates, and direct approaches include inoculation with specific probiotic microbes, artificial microbial consortia, and microbiome breeding and transplantation. We highlight why and how microbiome services could be incorporated into traditional agricultural practices and the gaps in knowledge that must be answered before these approaches can be commercialized in field applications. Highlights: Symbiotic bacteria can boost plant growth, control pathogens, or alleviate abiotic stress. Microbiome engineering incorporated into traditional agricultural practices can improve microbial ecosystem services for crop yield and resilience. New agricultural practices may include microbiome breeding, transplantation, and targeted microbiome engineering, for example by strategic soil amendments in which selective addition of plant exudates attracts and maintains beneficial microbes, or by directly applying microbial consortia as probiotics. Customized microbiome engineering will be necessary to cope with the many variables, including soil type, environmental/climatic conditions, growth stage, and genotype of the plant, to influence the microbiome in a purposeful and effective manner. Breeding 'microbe-friendly' crops can complement microbiome engineering to better attract and maintain beneficial microbiomes.